Extremely efficient quantum-cutting Cr3+, Ce3+, Yb3+ tridoped perovskite quantum dots for highly enhancing the ultraviolet response of Silicon photodetectors with external quantum efficiency exceeding 70%. (December 2020) - Ding, Nan; Xu, Wen; Zhou, Donglei; Ji, Yanan; Wang, Yue; Sun, Rui; Bai, Xue; Zhou, Ji; Song, Hongwei
Abstract: Silicon (Si) photodetectors (PDs) have been extensively utilized as an attractive building block for optoelectronic devices, but are limited by the weak ultraviolet (UV) photo-response. Herein, we employ the extremely efficient UV to near-infrared quantum cutting emissions to boost the UV response of Si PDs for the first time. Experimental and theoretical results demonstrate the Cr 3+, Yb 3+, Ce 3+ tri-doped CsPbCl3 perovskite quantum dots (PeQDs) are successfully fabricated, with the photoluminescent quantum yields (PLQYs) of 188% and excellent stability, which can be attributed to the enhanced exciton binding energy, reduced defects and high tolerance factor through Cr 3+ doping, and the improved energy transfer from PeQDs to Yb 3+ via bridging the energy gap by Ce 3+ doping. Meanwhile, the 5 d high energy states of Ce 3+ ions significantly enhance UV absorption of PeQDs. Through integrating PeQDs with Si PDs, it realizes the full spectrum response spanning from 200 nm to 1100 nm with excellent stability. Especially, their external quantum efficiency (EQE) exceeds 70% in the range of 200–400 nm, which is the highest one compared to the previous literatures. The findings highlight a powerful tool to improve the quantum cutting emissions and expand their PDs applications. Graphical abstract: Schematic diagram on Si PDs integrating with quantum cutting CsPbCl3 :Cr 3+, Yb 3+, Ce 3+ PeQDs under full lights illumination. Image 1 Highlights: We employ the extremely efficient UV to near-infrared quantum cutting emissions to boost the UV response of Silicon photodetectors. The Cr 3+, Yb 3+, Ce 3+  tri-doped CsPbCl3  PeQDs are successfully fabricated, with the PLQYs of 188%. The 5 d  high energy states of Ce 3+  ions significantly enhance UV absorption of PeQDs and it realizes the full spectrum response spanning from 200 nm to 1100 nm. Especially, the EQE exceeds 70% in the range of 200–400 nm, which is the highest one compared to the previous literatures.